E-participation: A systematic understanding on public participation in the government in 21st century / Nur Rusydina Khadzali and Zainal Md. Zan - Khadzali, Nur Rusydina; Md. Zan, Zainal (Universiti Teknologi MARA, Perlis, 2018)
Public participation has been a subject of active discussion in many fields particularly in political and administrative science. This concept emerges when public became, to a large extent, more concerned about the involvement in governmental decision-making processes than they had been before. In most of the countries, public participation issue increasingly catches the interest of the academics, practitioners, regulators as well as the governments. Currently, with the extraordinary growth of information and communication technologies (ICT), e-participation has been proposed to indicate the integration of ICT purposely to support the traditional participatory process. It is believed that these technologies namely the internet has made it possible for the public to easily communicate, deliberate, and collaborate. Eparticipation helps to improvise public involvement in the government as it serves to encourage two-way communication between the government and citizens, educate citizens on the underlying principle and complexity of policy-making, legitimize government decisions, and provide opportunities for mutual learning. Theoretically, e-participation seems to open huge possibilities and various benefit to the public as well as to the government than the traditional way of participation. Yet, either it is traditional participation or e-participation, public knowledge and understanding remained unclear. Therefore, this paper attempts to explore the concept of this subject matter in comprehensively manne